Case Report : Caecal Endometrios is Causing Acute Small Bowel Obstruction - Halim, Freda S. (Medicinus, 2019)
Introduction: Endometriosis in bowel is rare condition, about 12% of endometriosis cases. Most of bowel endometriosis rising in the rectosigmoid (90% of bowel endometriosis). Incidence of caecal endometriosis is very low (<5% of bowel endometriosis) and almost never causing acute small bowel obstruction(0.1-0.7%). The aim of this paper is to show that although  bowel obstruction caused by caecal endometriosis is difficult to diagnose as it is rare, and may require laparotomy to make definite diagnosis, but it should be considered in infertile female patient. Case: 37 years old woman infertile woman with intestinal obstruction with pre-operative diagnosis total acute small bowel obstruction caused by right colonic mass, with sepsis as the complication. Before the acute small bowel obstruction she complained of chronic right lower quadrant pain with chronic constipation alternate with chronic diarrhea, symptoms that happened both in bowel endometriosis and colorectal malignancy. She also complained of  chronic pelvic pain and dysmenorrhea. She has been married for 10 years with no child. The patient was never diagnosed with endometriosis and never seek medical attention for the infertility and the chronic pelvic pain. The patient underwent Abdominal CT Scan, with result:  massive small bowel obstruction, and caecal mass that causing acute small bowel obstruction. Diagnosis of Acute small bowel obstruction due to right colonic mass was made and emergency exploratory laparotomy was performed the patient. Methods: During the laparotomy, mass at caecum and ileocaecal that causing massive small bowel obstruction was found and standard right hemicolectomy and temporary mucousfistula ileostomy was performed. Result: The patient recovered well, discharged on 7th day post op. The pathology examination showed  ectopic endometriosis lesions in caecum and ileocaecal valve. The histopathology also confirmed with the immunohistochemistry, in which positive ER, PR, CD 10 and CD7 was found the ileocaecal and caecal mass. In the second operation,  reanastomosis of the ileum was done 3 months after the first operation. The chronic pelvic pain is decreasing dramatically after the first and second operation. Conclusion: Although bowel obstruction caused by caecal endometriosis is an extremely rare cause of intestinal obstruction but it   should be considered as a cause in infertile female patient to reduce morbidity and mortality, to reduce stoma creation and to promote resection completeness.